A methodological approach for structural health monitoring of mass-timber buildings under construction. (25th January 2021) - Baas, Esther J.; Riggio, Mariapaola; Barbosa, André R.
Highlights: A methodological approach to managing monitoring data of mass timber buildings is proposed. The approach is validated using ten months of hygrothermal and static monitoring data. Data describe moisture performance of roof panels, and tension loss in post-tensioned shear walls. Abstract: Structural health monitoring (SHM) is a method used to evaluate the performance of new structural systems and critical infrastructure. With mass-timber building construction on the rise, SHM programs have emerged to document hygrothermal, static, and dynamic behavior of these structures. To most efficiently document behavior and provide recommendations to industry, it is key that the research community work collaboratively to create consistent data by using standardized approaches. This paper presents a methodological approach for monitoring mass-timber buildings during construction to address this need. The approach was validated over ten months with a mass-timber building under construction at Oregon State University.